2019
DOI: 10.3390/s19030745
|View full text |Cite
|
Sign up to set email alerts
|

Research on Damage Detection of a 3D Steel Frame Model Using Smartphones

Abstract: Smartphones which are built into the suite of sensors, network transmission, data storage, and embedded processing capabilities provide a wide range of response measurement opportunities for structural health monitoring (SHM). The objective of this work was to evaluate and validate the use of smartphones for monitoring damage states in a three-dimensional (3D) steel frame structure subjected to shaking table earthquake excitation. The steel frame is a single-layer structure with four viscous dampers mounted at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 35 publications
0
17
0
Order By: Relevance
“…A study demonstrated the feasibility of using smartphones to monitor the response of a building structure subjected to extreme events, such as earthquakes. The importance of carrying out a practical study to validate the application was also stressed [7]. For this reason, it is important that the inventiveness of such applications starts in basic education.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A study demonstrated the feasibility of using smartphones to monitor the response of a building structure subjected to extreme events, such as earthquakes. The importance of carrying out a practical study to validate the application was also stressed [7]. For this reason, it is important that the inventiveness of such applications starts in basic education.…”
Section: Resultsmentioning
confidence: 99%
“…Another disadvantage of transferring vibrations to the support base is that the mass and elasticity of the base have an effect on the frequency of oscillation, which can cause an undesirable change in frequency and smartphones can also be used to monitor this condition. by measuring threedimensional acceleration in a given space and biaxial displacement in a given plane [7].…”
Section: Introductionmentioning
confidence: 99%
“…Aiming to decrease monitoring costs and enable public participation, the application quantity of using smartphones in SHM is increasing fast. These applications include pedestrian link bridge vibration monitoring [24], in-plane displacement monitoring [25], three-dimension steel frame model damage detection [26], three-dimension displacement monitoring [27], building dynamic characteristics monitoring [28,29], bridge seismic monitoring [30]. Among these applications, the following three applications used smartphones to monitor displacement.…”
Section: Introductionmentioning
confidence: 99%
“…Zhao et al [25] used a smartphone and a laser point to monitor displacement in the laboratory and verify the feasibility of an app called D-Viewer. Xie et al [26] used this method to record the displacement history of a shaking table test of a three-dimensional steel frame. Wang et al [27] developed this method and made this App be able to monitor the out-of-plane displacement.…”
Section: Introductionmentioning
confidence: 99%
“…Li et al [ 8 ] utilized the camera of smartphone to measure the interstory drift of building structures during earthquakes. Xie et al [ 9 ] conducted an experiment to verify the feasibility of using smartphones to perform structural damage detection of a 3-D steel frame structure. Matarazzo et al [ 10 ] and Ozer et al [ 11 ] proposed to use smartphones to identify the bridge’s modal frequencies, which provides a low-cost and efficient method to collect the structural health condition data of the bridges.…”
Section: Introductionmentioning
confidence: 99%